RF gun for ILU-12 accelerator - Auslender, V.L.; Gornakov, I.V.; Kuznetsov, G.I.; Makarov, I.G.; Matyash, N.V.; Ostreiko, G.N.; Panfilov, A.D.; Serdobintsev, G.V.; Tarnetsky, V.V.; Tiunov, M.A. (Вопросы атомной науки и техники, 2008)
RF gun for ILU-12 accelerator is described in the paper. Mechanism of beam transportation and energy spectrum improvements by applying an additional RF voltage of the operating frequency to the cathode-grid gap is considered in detail. Simulated energy spectrum and density profile of electron beam at the accelerator output are presented.